2017
DOI: 10.1093/biolre/iox014
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic profiling of endometrial fluid in women with ovarian endometriosis†

Abstract: The proteomic content of the endometrial fluid (EF) from patients with endometriosis has been investigated, but the lipidomic profile has not been analyzed yet in detail.This study is a comparative untargeted lipidomic analysis of human EF obtained from 35 patients (12 endometriosis and 23 controls). Global differential lipidomic profile was analyzed in both groups by ultrahigh performance liquid chromatography coupled to mass spectrometry. A total of 123 out of the 457 metabolites identified in the EF were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 22 publications
1
27
0
Order By: Relevance
“…Our results show that functions such as metabolism and biosynthesis of steroids and lipids were enriched in oocytes from women with endometriosis compared to oocytes from healthy donors. Lipid dysregulation in serum (Dutta et al, 2016) and endometrial fluid (Domínguez et al, 2017) has been demonstrated in both mouse models and women with endometriosis, as well as altered steroidogenesis in human granulosa cells (GCs) (…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that functions such as metabolism and biosynthesis of steroids and lipids were enriched in oocytes from women with endometriosis compared to oocytes from healthy donors. Lipid dysregulation in serum (Dutta et al, 2016) and endometrial fluid (Domínguez et al, 2017) has been demonstrated in both mouse models and women with endometriosis, as well as altered steroidogenesis in human granulosa cells (GCs) (…”
Section: Discussionmentioning
confidence: 99%
“…Despite several studies on metabolomics in various diseases, use of this approach is still sparse in endometriosis 10 12 . NMR and MS based metabolomics studies on endometrial fluid 13 , follicular fluid 14 , urine 10 , serum 15 and plasma 16 of endometriosis women have shown remarkable changes in their metabolite profile. Since endometrial tissue communicates with the blood directly or through extracellular fluids, several metabolites may be secreted into the blood stream.…”
Section: Introductionmentioning
confidence: 99%
“…The model presented here revealed that triacylglycerol (TG) and α‐amino acids are metabolites overs abundant in patients presenting with endometriosis. Intriguingly, Domínguez et al (), found reduced levels of saturated diacylglycerols and saturated TGs in the endometrial fluid of patients with endometriosis when compared with controls. Excessive accumulation of TGs, however, is associated with human diseases such as obesity, diabetes mellitus, and steatohepatitis.…”
Section: Discussionmentioning
confidence: 96%